PENGARUH LAMA PENYULINGAN DAN KOMPOSISI BAHAN BAKU TERHADAP RENDEMEN DAN MUTU MINYAK ATSIRI DARI DAUN DAN BATANG NILAM (Pogostemon cablin Benth) - A Sulaiman (Jurnal Riset Industri Hasil Hutan, 2012)
The research of Distillation And Raw Material Composition Effect of Yield And Quality EssentialOil of Leaves And Stem Patchouli (Pogostemon cablin Benth). This study aimed to examine the influence of the length of distillation and composition of raw materials to the yield and quality of essential oil of patchouli leaves and stems to produce essential oils that have a high quality and yield. The time required to obtain the highest yield of patchouli oil is 8 hours, by composition of 100% leaf (1:0), that is equal to 3.631%, while the lowest yield of patchouli oil are produced from 100% stem (1:0) by distillation of 4 hours, in the amount of 0.10%. Composition that produces patchouli oil with the best quality is 100% stems (0:1) but that yield is lower, while the quality of patchouli oil produced by 100% leaf (1:0) and a mixture of leaf-stem (1:1) quality is still lower than the patchouli oil from the stem, but its yield is better than the yield of oil patchouli by 100% composition of the stem (0:1).Keywords:  essential oil, pogostemon cablin benth, yield